Collaborative Research (CR) as a reduced transaction cost in Open Innovation - Porath, Amiram (2012)
In this conceptual paper, open innovation is considered from the point of view of collaboration between industry and academy. However, if considered under the framework of the Resource Based Theory, specifically regarding Transaction Cost, it can be shown that the two phenomena are in fact compatible. The discussion regarding Transaction Cost is focused mainly on the management resources available for the activity and the cost incurred as alternative cost compared to other activities the management could engage in, especially regarding the nexus of Industry-Academy collaboration. SMEs faced with the ever increasing stress of intensive competition and limited by their resources in their abilities to deal with it effectively turn to collaboration as a solution. The discussion synthesizes two articles recently published as chapters in books (Porath, 2012a; Porath, 2012b) analyzing collaboration as an open innovation activity within the Resource Based Theory.